Investigation of the presence of slime production, VanA gene and antiseptic resistance genes in Staphylococci isolated from bovine mastitis in Algeria - Saidi, Radhwane (Array, 2020)
Staphylococcus strains are frequently as- sociated with clinical and subclinical bovine intra-mammary infection. The virulence factors of staphylococcus have not been widely studied in Algeria. The objective of this study was to determine the frequency of slime production, VanA gene and antiseptic resistance genes in staphylococci strains isolated from bovine mas- titis in Algeria. The study examined 35 Staphy- lococci strains obtained from the inflammatory secretion of mammary glands of cows with mastitis. Slime production was determined by detecting the icaA and icaD genes using the polymerase chain reaction (PCR) method and Congo red agar (CRA) method. The presence of qacAB and qac C antiseptic resistance genes and the VanA resistance gene in these isolates was investigated by PCR. The results of the current study revealed that of the 35 Staphylo- cocci isolates, 42.85% (15/35) and 17.14% (6/35) of the isolates harboured the slime production gene by analysing icaA and icaD genes, respec- tively and 71.42% (25/35) by the CRA method. However, VanA and antiseptic resistance genes (qacAB and qac C) were not detected in any of the isolates. Therefore, the majority of Staphylo- coccus strains were capable of producing slime, and the CRA detection rate was higher than the PCR method for the biofilm-producing capac- ity of Staphylococcus strains. Thus, the presence of the ica genes in Staphylococcus strains con- firms its role as a virulence factor in the patho- genesis of bovine mastitis.